Peningkatan Pengetahuan Anak Usia Dini Tentang Kebersihan Diri dan Kesehatan Mulut di Kota Bengkulu - Nurhayati Nurhayati; Fatsiwi Nunik Andari; Padila Padila; Andry Sartika (Gayaku Publisher, 2022)
Early childhood education is a level before basic education or pre-school which is a coaching effort to help stimulate growth and physical and spiritual development of children so that they are ready to enter further education. In pre-school children, health problems related to general health, developmental disorders, behavioral disorders, and learning disorders often arise. Health problems that are generally encountered are diarrhea, intestinal worms, lack of personal hygiene, and dental health problems, so this requires special attention from parents, teachers, and health practitioners. To support and contribute actively in monitoring health problems in pre-school age children, community service activities in the health sector are needed. This community service activity was carried out through health education for students to increase knowledge and understanding of clean living behavior regarding personal hygiene and oral health. From the evaluation results, it was found that there was an increase in students' understanding of clean and healthy living behaviors and being able to demonstrate how to wash hands and brush their teeth properly.